Impacts of the Covid-19 pandemic on internal corporate communication: literature review (Research, Society and Development, 2022)
The purpose of this article is to discuss the impacts that the Covid-19 pandemic has had on companies’ internal communication. A scoping literature review was carried out from Google Scholar searches to map studies published to which inclusion and exclusion criteria were applied. The results indicated that there was not enough time for companies to adapt adequately to remote work, which generated negative emotions in employees, such as worry, anxiety, and helplessness. One of the aspects that amplified these negative impacts was the difficulty in properly reconciling the work and home environments. The organizations then adopted digital tools for communication with their collaborators, aiming to welcome, integrate and motivate them, concerned with their physical and emotional health. However, the low proficiency in digital skills on the part of managers and employees may have contributed to introducing noise in communication. The article concludes that the internal communication of organizations needs to be continuous and planned for the long term, with the insertion of humanized elements, especially in times of crisis, as was the pandemic of Covid-19, to strengthen the affective bonds between the parties. In addition, it is necessary to establish more detailed rules for remote work that respect employees’ well-being.